Biosafety: The Safe Application of Biotechnology in Agriculture and the Environment - Persley, Gabrielle J.; Giddings, L. V.; Juma, Calestous (International Service for National Agricultural Research, 1993)
The purpose of this document is to review the development of modern biotechnology and provide guidance for policymakers and research managers who need to ensure that new biotechnology products are used safely in their country.